2013
DOI: 10.1001/jamaophthalmol.2013.5599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemodialysis on Intraocular Pressure and Ocular Perfusion Pressure

Abstract: IMPORTANCE Elevated intraocular pressure (IOP) and decreased ocular perfusion pressure (OPP) are risk factors for glaucoma development and progression. Unrecognized significant IOP elevation or OPP reduction during hemodialysis (HD) could lead to glaucomatous optic nerve damage and subsequent visual loss. OBJECTIVE To evaluate changes in IOP and OPP during HD. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional observational study was conducted in patients undergoing HD at an ambulatory care clinic at the Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
4
33
0
6
Order By: Relevance
“…IOP is especially important for treating glaucoma. Although intraocular hypertension is not a requirement, it is still a significant risk factor in the development of glaucoma treatment (7,8). Lowering the IOP level is also the only effective treatment means to control the development of glaucoma in clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…IOP is especially important for treating glaucoma. Although intraocular hypertension is not a requirement, it is still a significant risk factor in the development of glaucoma treatment (7,8). Lowering the IOP level is also the only effective treatment means to control the development of glaucoma in clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…8 There was a significant decrease in plasma osmolality and a significant increase in colloidal osmotic pressure, but neither of these correlated with IOP changes, which in themselves were significant. 8 There was a significant decrease in plasma osmolality and a significant increase in colloidal osmotic pressure, but neither of these correlated with IOP changes, which in themselves were significant.…”
Section: Rise In Iop With Hdmentioning
confidence: 83%
“…A recent study conducted in 49 patients found a significant increase in IOP and a decrease in OPP with HD. 8 There was a significant decrease in plasma osmolality and a significant increase in colloidal osmotic pressure, but neither of these correlated with IOP changes, which in themselves were significant. Instead, the authors found a significant relationship between IOP and OPP.…”
Section: Rise In Iop With Hdmentioning
confidence: 83%
“…15 Hu et al did not show a correlation with an increase in colloid osmotic pressures and decreased IOP. 25 They were able to show a positive correlation between increased ultrafiltration and increased colloid osmotic pressure.…”
Section: Increasing Fluid Removalmentioning
confidence: 96%